Intention-based walking support for paraplegia patients with Robot Suit HAL - Suzuki, Kenta; Mito, Gouji; Kawamoto, Hiroaki; Hasegawa, Yasuhisa; Sankai, Yoshiyuki (Advanced robotics, 2007)
This paper proposes an algorithm to estimate human intentions related to walking in order to comfortably and safely support a paraplegia patient's walk. Robot Suit HAL (Hybrid Assistive Limb) has been developed for enhancement of a healthy person's activities and for support of a physically challenged person's daily life. The assisting method based on bioelectrical signals such as myoelectricity successfully supports a healthy person's walking. These bioelectrical signals, however, cannot be measured properly from a paraplegia patient. Therefore another interface that can estimate a patient's intentions without any manual controller is desired for robot control since a manual controller deprives a patient of his/her hand freedom. Estimation of a patient's intentions contributes to providing not only comfortable support but also safe support, because any inconformity between the robot suit motion and the patient motion results in his/her stumbling or falling. The proposed algorithm estimates a patient's intentions from a floor reaction force (FRF) reflecting a patient's weight shift during walking and standing. The effectiveness of this algorithm is investigated through experiments on a paraplegia patient who has a sensory paralysis on both legs, especially his left leg. We show that HAL supports the patient's walk properly, estimating his intentions based on the FRF, while he keeps his own balance by himself.